Effects of caffeine, beetroot juice and its interaction consumption on exercise-related fatigue - Castillo, Daniel (Array, 2021)
The aim of this study was to analyze the effect of different supplementation conditions on fatigue and performance in flywheel half-squat tests in senior men. Sixteen active males (age: 22.8±4.9 years; body mass index: 23.7±2.4 kgm-2) participated in the intervention during a 4-week period. Four experimental conditions were established using a double-blind design: placebo, caffeine (CAF), beetroot juice (BRJ), and combined BRJ+CAF. To assess the effect of supplementation, participants completed a countermovement jump (CMJ) before (Pre), 30 s after (Post-30s) and 180 s after (Post-180 s) completing a flywheel half-squat exercise protocol (four sets of eight all-out repetitions, with 3-min inter-set rest, using different inertial loads). Additionally, the mean power output during the flywheel half-squat protocol was recorded.